THE RIGHT TO MENTAL HEALTH WITHIN THE BRAZILIAN JURIDICAL-CRIMINAL SYSTEM AND THE MAINTENANCE OF THE DIGNITY OF THE PERSON WITH MENTAL DISORDER IN CONFLICT WITH THE LAW - Ferreira Júnior, Armando; Cleuder de Melo, Bruno; Henrique Medeiros de Souza, Carlos; Lacerda Tinoco Boechat Cabral, Hildeliza (LINKSCIENCEPLACE, 2026)
The problem of the present research focuses on the way in which the legal-prison system treats people affected by a mental disorder who committed crimes, since following the treatment of the Penal Execution Law, many are still referred to hospitals for custody and psychiatric treatment (HCTP) contrary to what the anti-asylum movement proposes. The purpose of this study is to discuss the predictions of the Criminal Enforcement Law and the Brazilian Psychiatric Reform Law in order to understand how the Brazilian State has dealt with the conflicts between the two laws and to know the actions promoted by the Judiciary and by the Federal Government (Sistema Único de Saúde - SUS and Sistema Único de Asistencia Social - SUAS) in order to promote the adaptation of the legal-prison system to the anti-asylum fight. The relevance of the proposed theme is evidenced by factors such as the worrying increase in the prison population, the slowness of the Judiciary Power in view of the large number of preventive prisons, the deleterious effects of incarceration and the worsening of the conditions of the accused person suffering from the disorder due to their incarceration in an HCTP due to the impediment or difficulty of accessing relatives. The methodology implemented in the present study is based on the bibliographic review allowing the analysis of the pertinent legislation, as well as other similar studies that allow to increase the knowledge about the conditions of people with mental disorder in conflict with the law and the successful measures that have been adopted in order to promote the deinstitutionalization of people with HCTP mental disorders.